A Critical Realist Review of JKN-BPJS Implementation in Indonesia - Langingi, Nova Lina; Tuppal, Cyruz P. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Through the National Health Insurance (JKN) organized by Social Security Administrative Bodies-Health (BPJS Kesehatan), the country is present to ensure that all Indonesian citizens are protected by comprehensive, fair, and equitable health insurance. The implementation and existence of the National Health Insurance (JKN) program have been highly beneficial for the public. Unfortunately, there is half of the total population who do not have full coverage of essential health services to investigate the implementation of JKN-BPJS in Indonesia. A critical realist review focuses on the study of JKN-BPJS Implementation as a whole in Health care agencies, namely hospitals and Puskesmas (Primary Health Care) in Indonesia used the google search engine in searching, with the keywords of "implementation of JKN-BPJS" and "execution of JKN-BPJS" because of this study specifically about Indonesian Health Insurance. The appraisal tool to assess the qualitative study used by the researcher was a tool from the Alberta Heritage Foundation of Medical Research. After assessing seven articles, the researcher found six articles with a score > 80% and one article with only a 55% score, and thus, six articles meet the criteria. There were two themes in this study, namely compliments and room for improvement. Furthermore, each theme has sub-themes. Compliments have eight sub-themes: facility and infrastructure; attitude; knowledge, skill, continuing education; coordination; communication; standard operating procedure; socialization; and commitment. Lastly, room for improvements has five sub-themes: facility and infrastructure; workload; attitude; communication; and socialization. It is recommended to the Health Care Agency (Hospital and Health Care Agency) to add and improve the facilities and infrastructures such as the number of beds and patient rooms and add healthcare workers and administrative staff. Keywords : JKN-BPJS, Indonesia, Implementation